Polymer blends
By mixing the reactions of polyester-polyether embedded segments and polyacrylate parts with amino sibidane, it solves the difficulty of dealing with the existing thermoplastic curing rubber in the processing process. The high efficiency, safety and aesthetics of common mixed objects.
Patent Information
- Application Number
- CN202080091186.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-05-13
- Filing Date
- 2020-12-22
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2040-12-22
AI Technical Summary
Existing thermoplastic cured rubber and other elastomer blends have difficult properties during processing, including the use of hazardous reagents, hazardous conditions for irradiation crosslinking, slow reaction rates, polymer degradation, undesirable viscosity, gels Defects, dark spots and other impurities make processing difficult.
The polyester-polyether embedded parts and polyacrylate clusters are mixed with the reaction product of amino silane, and the processing characteristics of the co-mixture of the polymer are improved through the relatively safe and efficient cross-linked agent of amino silane.
A new type of polymer used under the harsh conditions has been realized, the safety and efficiency of the production process are improved, and the aesthetic quality of the polymer co -mixture is improved.
Smart Images

Figure BDA0003723404290000071 
Figure BDA0003723404290000072 
Figure BDA0003723404290000111
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims priority under 35 U.S.C. §365 to U.S. Provisional Application No. 62 / 956,070, filed on December 31, 2019, and U.S. Provisional Application No. 63 / 024,510, filed on May 13, 2020, each of which is incorporated herein by reference in its entirety. Technical Field
[0003] The present invention relates to polymer blends comprising the reaction product of a polyether-polyester block copolymer and a polyacrylate copolymer with an aminosilane; methods of producing these polymer blends; and articles comprising these polymer blends. Background Art
[0004] Several patents, patent applications and publications are cited in this specification to more fully describe the state of the art to which the present invention relates. The entire disclosure of each of these patents, patent applications and publications is incorporated herein by reference.
[0005] Polymer blends are key materials used in the manufacture of a wide variety of consumer products and industrial devices. Therefore, there is a continuing interest and importance in improving the properties, synthesis, processing, economics, and appearance of polymer blends.
[0006] A well-known method for realizing the improvement of polymer composition is to carry out by blending two or more polymers.The combination of polymers can provide one or more advantages in the individual components.For example, a relatively expensive material with a desired physical property can be combined with a cheaper material to produce a polymer blend with a more favorable cost and performance balance.
[0007] Elastomers are an important class of polymers with desirable properties and widespread utility in many industries, and blends of various types of elastomers are known. Elastomer blends can contain two or more elastomers, or they can contain one or more elastomers with one or more non-elastomeric polymers. Elastomer blends can be alloys or solid solutions, such as when one or more elastomers are miscible with one or more other polymers. When a blend contains two or more immiscible polymers, other morphologies are possible, such as dispersions and co-continuous blends.
[0008] One type of blend that can contain an elastomer is a thermoplastic vulcanizate ("TPV"), which comprises a thermoplastic phase and a "cured" or crosslinked elastomeric phase. TPVs combine many of the desirable features of crosslinked or cured rubbers with certain features of thermoplastic resins. For example, TPVs can be melt processed using thermoplastic resin processing equipment, such as an extruder. Due to the excellent tear strength, tensile strength, flex life, chemical resistance, and wide end-use temperature range of TPVs, TPVs (especially copolyether-ester TPVs, such as those described in International Patent Application Publication No. WO 2004 / 029155) are used in a wide range of applications, including the manufacture of articles for use in the fields of automotive, wire and cable, fluid power, electrical and electronic applications, hoses and pipes, and appliances.
[0009] In this regard, US Pat. No. 6,448,343 to Schombourg et al. describes a TPV comprising two polymers, one of which is grafted or copolymerized with a carboxylic anhydride, the anhydride-grafted polymer then reacted with an aminosilane which reacts with the anhydride and then crosslinks the one polymer.
[0010] Additionally, US Pat. No. 7,074,857 to Bendler et al. describes a curable thermoplastic elastomer blend comprising a polyalkylene phthalate polyester polymer or copolymer and a polyacrylate or polyethylene / acrylate rubber, and effective amounts of a peroxide free radical initiator and an organic diene crosslinking aid.
[0011] However, thermoplastic vulcanizates and other elastomeric blends can be difficult to process. Suboptimal selection of starting materials, reagents, and processing conditions can produce unfavorable properties or results, including, for example, hazardous reagents, such as peroxides; hazardous conditions, such as crosslinking by irradiation; slow reaction rates; polymer degradation, such as by exposure to radiation or free radicals; undesirable stickiness due to insufficient crosslinking levels or due to polymer degradation; formation of gel defects, black specks, and other impurities; extrusion die instability, manifested as surface roughness in extruded parts or lumps in blow molded parts; and processing difficulties due to excessive crosslinking (e.g., rubber scorch).
[0012] Therefore, it is still desirable to produce new polymer blends with properties tailored for use under harsh conditions.It is also still desirable to improve the methods of producing these polymer blends to increase their safety and efficiency and to improve the aesthetic qualities of the polymer blends. Summary of the invention
[0013] Thus, a polymer blend is provided herein, comprising a reaction product of a polyester-polyether block copolymer and a polyacrylate copolymer with an aminosilane. The polyester-polyether block copolymer comprises copolymerized residues of polybutylene terephthalate and copolymerized residues of polyether diol, and the polyacrylate copolymer comprises copolymerized residues of an anhydride cure site comonomer.
[0014] Further provided are methods for preparing the polymer blends. In a first method, a polyacrylate copolymer and an aminosilane are combined, and in a second step, a polyester-polyether block copolymer is added and melt mixed. In a second method, a polyester-polyether block copolymer, a polyacrylate copolymer, and an aminosilane are combined in a melt.
[0015] Further provided are articles comprising the polymer blends, such as consumer electronics (power cord jackets and strain reliefs); consumer products, such as footwear outsoles and midsoles; soft touch overmolding for power tools and other handheld devices, wearable applications, such as belts or strips, and sealing applications, such as automotive intake manifold gaskets; wire and cable applications, such as jackets; oil and gas flat packs; automotive shields, such as inboard and outboard constant velocity joint (CVJ) shields, drive shaft shields, and diaphragm shields; and air ducts for transportation vehicles such as automobiles. These articles can be made by typical methods for making with thermoplastic or thermosetting polymers. DETAILED DESCRIPTION
[0016] Unless otherwise defined, all technical and scientific terms used herein have the same meanings as those generally understood by those of ordinary skill in the art to which the invention belongs. Although methods and materials similar or equivalent to the methods and materials described herein can be used in the practice or testing of embodiments of the invention, suitable methods and materials are described below. The materials, methods, and examples described herein are illustrative only and are not intended to be limiting.
[0017] As used herein, the terms "comprises," "comprising," "includes," "including," "has," "having," "contain," "containing," or any other variation thereof, refer to a non-exclusive inclusion. For example, a process, method, article, or apparatus that comprises a list of elements is not necessarily limited to those elements but may include other elements not expressly listed or inherent to such process, method, article, or apparatus.
[0018] The transitional phrase "consisting essentially of limits the scope of a claim to the specified materials or steps and those that do not materially affect one or more basic and novel features of the claimed invention. "A 'consisting essentially of' claim is intermediate between closed claims written in 'consisting of' format and fully open claims written in 'comprising' format." Where an invention or a portion of an invention is described using an open-ended term such as "comprising," it should be understood that the description also includes descriptions of inventions using the terms "consisting of" and "consisting essentially of," unless otherwise indicated in specific instances.
[0019] As used herein with respect to a phase or composition, the term "consisting essentially of" means that the phase or composition contains greater than 95% by weight or greater than 99% by weight of one or more of the components, based on the total weight of the polymer, phase or composition. Thus, the polymer, phase or composition to which this term applies may contain one or more other comonomers, components or additives, such as those described below, including any one or more carriers that may be introduced with the one or more other components or additives. In these amounts, the one or more other comonomers, components, additives and their carriers do not alter the basic and novel characteristics of the phase or composition described herein.
[0020] In addition, unless expressly stated to the contrary, "or" refers to an inclusive "or" and not to an exclusive "or". For example, condition A or B is satisfied by any of the following: A is true (or exists) and B is false (or does not exist), A is false (or does not exist) and B is true (or exists), and both A and B are true (or exist).
[0021] In addition, the indefinite article "a" or "an" is used to describe the elements and components of the present invention. This is done only for convenience and to give a general sense of the present invention. This description should be interpreted as including one or at least one, and the singular also includes the plural, unless otherwise expressly indicated in the case of limitation.
[0022] As used herein, the term "about" means that amounts, dimensions, formulations, parameters, and other quantities and features are not and need not be exact, but may be approximate and / or larger or smaller (as desired), reflecting tolerances, conversion factors, rounding, measurement errors, etc., and other factors known to those skilled in the art. In general, an amount, dimension, formulation, parameter, or other quantity or feature is "about" or "approximate" whether or not expressly stated to be so.
[0023] In addition, unless otherwise expressly stated in the case of limitation, the ranges listed herein include their endpoints. In addition, when an amount, concentration, or other value or parameter is given as a range, one or more preferred ranges, or a series of upper preferred values and lower preferred values, this should be understood to specifically disclose all ranges formed by any pairing of any upper range or preferred value with any lower range or preferred value, regardless of whether such pairing is disclosed separately.
[0024] However, when numerical ranges are described herein, unless otherwise indicated in specific cases, the ranges are intended to include their endpoints, as well as all integers, fractions, and real numbers within the range. It is not intended that the scope of the present invention be limited to the specific values recited when defining the range. Finally, when the term "about" is used to describe a value or an endpoint of a range, the disclosure should be understood to include the specific value or endpoint mentioned.
[0025] As used herein, the term "copolymer" refers to a polymer comprising copolymer units obtained by copolymerization of two or more comonomers. In this regard, the copolymer can be described herein with reference to its constituent comonomers or the amount of its constituent comonomers, such as "a copolymer comprising ethylene and 15% by weight of acrylic acid" or similar descriptions. Such a description can be considered informal because it does not refer to the comonomer as a comonomer; because it does not include the conventional nomenclature of copolymers, such as the International Union of Pure and Applied Chemistry (IUPAC) nomenclature; because it does not use the terminology of the product defined by the method; or for another reason. As used herein, however, the description of the copolymer with reference to its constituent comonomers or the amount of its constituent comonomers means that the copolymer contains copolymer units (in a specified amount when specified) of the specified comonomer. The terms "unit" and "residue" are synonymous and are used interchangeably herein with respect to the constituent comonomers of the copolymer. As a corollary, a copolymer is not the product of a reaction mixture containing a given amount of a given comonomer, unless it is explicitly stated to be so in a limited case.
[0026] The term "(meth)acrylate" as used herein, alone or in combination (eg, "(meth)acrylate"), refers to acrylate or methacrylate, for example, "acrylic acid or methacrylic acid," or "alkyl acrylate or methacrylate."
[0027] The terms "copolyether-ester polymer," "polyether-polyester block copolymer," and "polyester-polyether block copolymer" are synonymous and used interchangeably herein. Some, but not all, polyester-polyether block copolymers are elastomeric.
[0028] As used herein, the term "thermoplastic vulcanizate" ("TPV") refers to a polymeric material having a crosslinked rubber phase dispersed in a continuous thermoplastic phase.
[0029] As used herein, the term "polymer blend" refers to a melt-processible polymeric material having a crosslinked rubber phase and a thermoplastic phase.
[0030] Provided herein is a polymer blend comprising the reaction product of a copolyether-ester polymer and a polyacrylate copolymer with an aminosilane.
[0031] Advantageously, aminosilanes are relatively safe and effective crosslinking agents. They do not share the disadvantages of free radical crosslinking such as that produced by peroxides or irradiation. In addition, the lower reactivity of aminosilanes compared to many peroxides results in safer storage and handling. For example, aminosilane crosslinking is not inhibited by the presence of antioxidants that are peculiar to free radical reactions. In addition, the polymer components in the aminosilane crosslinked polymer composition are not degraded by reacting with free radicals, and the formation of black spots or other impurities that may be caused by uncontrolled oxidation is not observed.
[0032] Aminosilanes also offer several advantages over polyamine crosslinking. The ester bonds in copolyether-ester polymers can be degraded by amines, and the reduced amine content of aminosilanes relative to polyamines minimizes these undesirable side reactions. In addition, polyamine curing agents grafted onto polyacrylate copolymers may leave dangling amine functionality that remains reactive during subsequent processing and adversely affects the extrusion quality of the polymer blend. In contrast, the silane functionality of aminosilanes undergoes hydrolysis and condensation even at room temperature. Thus, any residual reactivity during storage is eliminated. Finally, aminosilanes offer a range of options for selecting the reactivity of these two parts, thereby reducing the technical effort required to balance crosslinking and processing options for various polymer blends, TPV compositions.
[0033] Suitable polyester-polyether block copolymers are described in International Patent Application Publication No. WO2020 / 047406 by Szekely et al. However, in brief, suitable polyester-polyether block copolymers have multiple repeating long-chain ester units and short-chain ester units connected head to tail by ester bonds, and the long-chain ester units are represented by formula (A):
[0034]
[0035] And the short-chain ester unit is represented by formula (B):
[0036]
[0037] in
[0038] G is a divalent group remaining after removing the terminal hydroxyl group from a poly(alkylene oxide) glycol having a number average molecular weight between about 400 g / mol and about 6000 g / mol, or preferably between about 400 g / mol and about 3000 g / mol;
[0039] R is a divalent radical remaining after removing a carboxyl group from a dicarboxylic acid having a molecular weight of less than about 300 g / mol;
[0040] D is the divalent group remaining after removing the hydroxyl group from the diol having a molecular weight of less than about 250 g / mol.
[0041] The weight percentages of the copolymerized units of formula (A) and the copolymerized units of formula (B) in the copolyether-ester copolymer are complementary. That is, the sum of the weight percentages of the copolymerized units of formula (A) and the copolymerized units of formula (B) is 100 wt%. Similarly, the molar percentages of the R groups in the copolymerized units of formula (A) and the copolymerized units of formula (B) in the copolyether-ester copolymer are complementary. That is, the sum of the molar percentages of the R groups in the copolymerized units of formula (A) and the copolymerized units of formula (B) is 100 mol%.
[0042] As used herein, the term "long-chain ester unit" as applied to units in a polymer chain refers to the reaction product of a long-chain glycol and a dicarboxylic acid. Suitable long-chain glycols are poly(alkylene oxide) glycols having a terminal (or as close to the terminal as possible) hydroxyl group and having a number average molecular weight from about 400 g / mol to about 6000 g / mol, and preferably from about 600 g / mol to about 3000 g / mol. Preferred poly(alkylene oxide) glycols include poly(oxacyclopentane) glycols, poly(oxacyclobutane) glycols, poly(propylene oxide) glycols, poly(ethylene oxide) glycols, copolymer glycols of these alkylene oxides, and block copolymers such as poly(propylene oxide) glycols terminated with ethylene oxide. A mixture of two or more of these glycols can be used. The long-chain ester unit of formula (A) can also be referred to as the "soft segment" of a copolyether-ester polymer.
[0043] As used herein, the term "short-chain ester units" as applied to units in the polymer chain of copolyether-esters refers to low molecular weight compounds or polymer chain units having a molecular weight of less than about 550 g / mol. They are made by reacting a low molecular weight diol or a mixture of diols (molecular weight less than about 250 g / mol) with a dicarboxylic acid to form ester units represented by formula (B) above. The short-chain ester units of formula (B) may also be referred to as the "hard segments" of the copolyether-ester polymer.
[0044] Preferred low molecular weight diols that react to form short chain ester units are aliphatic diols containing 2 to 8 carbon atoms, and a more preferred diol is 1,4-butanediol. As used herein, the term "diol" includes equivalent ester-forming derivatives such as those mentioned. For example, ethylene oxide or ethylene carbonate may be used in place of ethylene glycol. The molecular weight refers to the diol, not the ester-forming derivative.
[0045] The dicarboxylic acids that can be reacted with the aforementioned long chain glycols and low molecular weight diols to form copolyether-esters are low molecular weight (i.e., having a molecular weight of less than about 300 g / mol) aliphatic, alicyclic or aromatic dicarboxylic acids. As used herein, the term "dicarboxylic acid" includes functional equivalents of dicarboxylic acids having two carboxyl functional groups that play a substantially similar role as dicarboxylic acids in reacting with glycols and diols to form copolyether-ester polymers. These equivalents include esters and ester-forming derivatives, such as acid halides and anhydrides. The requirement for molecular weight is for the acid, not its equivalent ester or ester-forming derivative.
[0046] Preferred are aromatic dicarboxylic acids. As used herein, the term "aromatic dicarboxylic acid" refers to a dicarboxylic acid having two carboxyl groups each attached to a carbon atom in an aromatic carbocyclic ring structure. It is not necessary that both functional carboxyl groups are attached to the same aromatic ring, and where more than one ring is present, they may be linked by an aliphatic or aromatic divalent group or a divalent group such as -O- or -SO2-.
[0047] Suitable aromatic dicarboxylic acids include phthalic acid, terephthalic acid and isophthalic acid; other phthalic acids; substituted dicarboxyl compounds having two benzene nuclei, such as bis(p-carboxyphenyl)methane; p-oxy-1,5-naphthalene dicarboxylic acid; 2,6-naphthalene dicarboxylic acid; 2,7-naphthalene dicarboxylic acid; 4,4'-sulfonyl dibenzoic acid and its C1-C 12 Alkyl and ring substituted derivatives, such as halo, alkoxy and aryl derivatives. Hydroxy acids, such as p-(β-hydroxyethoxy)benzoic acid, may also be used, provided that an aromatic dicarboxylic acid is also used. Preferred are aromatic acids having 8 to 16 carbon atoms, and more preferred are terephthalic acid, isophthalic acid, and a mixture of phthalic acid and isophthalic acid.
[0048] The copolyether-ester polymer preferably comprises from equal to or about 15 wt% to equal to or about 99 wt% of copolyether-ester units corresponding to the above formula (B), based on the total weight of the copolyether-ester, wherein the remaining weight of the copolyether-ester is composed of copolyether-ester units corresponding to the above formula (A). More preferably, the copolyether-ester polymer comprises from equal to or about 20 wt% to equal to or about 95 wt%, and even more preferably from equal to or about 30 wt% to equal to or about 90 wt%, or from equal to or about 50 wt% to equal to or about 90 wt% of copolyether-ester units, again wherein the remaining weight of the copolyether-ester is composed of copolyether-ester units.
[0049] More preferably, at least about 70 mole percent of the divalent groups represented by R in formulas (A) and (B) above are diradicals, and at least about 70 mole percent of the groups represented by D in formula (B) above are 1,4-butylene groups. In this more preferred copolyether-ester, the sum of the mole percent of R groups that are not 1,4-phenylene diradicals and the mole percent of D groups that are not 1,4-butylene groups does not exceed a unitless value of 30.
[0050] When a mixture of two or more dicarboxylic acids is used to prepare the copolyether-ester, isophthalic acid is the preferred secondary dicarboxylic acid. More preferred is a mixture of isophthalic acid and terephthalic acid. In a preferred mixture, for example, based on the total moles of the copolymerized dicarboxylic acid residues -(-C(O)RC(O)-)- in the copolyether-ester, the amount of the copolyisophthalate residues in the copolyether-ester is preferably less than 35 mol% or less than 30 mol%, more preferably less than 25 mol%, wherein the balance of the at least 70 mol% of the phenylene diradicals is derived from terephthalic acid. In some preferred embodiments, based on the total weight of the copolymerized dicarboxylic acid residues -(-C(O)RC(O)-)- in the copolyether-ester, the copolyisophthalate residues in the copolyether-ester are less than 35wt%, more preferably less than 25wt%. Likewise, in preferred mixtures, for example, the balance of the phenylene diradicals, based on the total weight of copolymerized dicarboxylic acid residues -(-C(O)RC(O)-)- in the copolyether-ester, is derived from terephthalic acid.
[0051] Preferred polymer blends include copolyether-ester polymers prepared from monomers including (1) poly(tetramethylene glycol) or poly(trimethylene glycol), poly(propylene glycol), poly(ethylene glycol), glycols containing residues of propylene oxide and ethylene oxide (EO / PO glycols), and mixtures of two or more of these; (2) dicarboxylic acids selected from the group consisting of isophthalic acid, terephthalic acid, and mixtures of two or more of these; and (3) diols selected from the group consisting of 1,4-butanediol, 1,3-propylene glycol, and mixtures of two or more of these. Furthermore, in preferred polymer blends, one or more of the copolyether-ester polymers are thermoplastic, i.e., they are melt processable and exhibit a melting peak temperature.
[0052] Particularly preferred are copolyether-esters having a hard segment consisting of polybutylene terephthalate and about 5 wt % or 10 wt % to about 70 wt % or 80 wt %, preferably about 10 wt % or 20 wt % to about 60 wt % of a soft segment consisting of a reaction product of a polyether glycol and an aromatic diacid. The polyether block is derived from polytetramethylene glycol and has a molecular weight of about 1000 g / mol to 2000 g / mol. Complementarily, the fraction of the hard segment is about 20 wt % or 30 wt % to 90 wt % or 95 wt %, preferably about 40 wt % to about 80 wt % or 90 wt %.
[0053] Suitable polyether-polyester copolymers are available from DuPont Specialty Products USA, LLC, of Wilmington, DE, as Trademark commercially available.
[0054] The polymer blends described herein also contain the reaction product of one or more polyacrylate copolymers and an aminosilane. Suitable polyacrylate copolymers are described in U.S. Pat. No. 8,779,044 to Steven R. Oriani. However, briefly, suitable acrylate copolymers are amorphous and include
[0055] a) at least 45 wt% or at least 50 wt%, based on the total weight of the amorphous acrylate copolymer, of copolymerized units of at least one monomer having the structure:
[0056]
[0057] Where R 1 Is H or C1-C 10 Alkyl, and R 2 It is C1-C 12 Alkyl, C1-C20 Alkoxyalkyl, C1-C 12 Cyanoalkyl, or C1-C 12 Fluoroalkyl; and
[0058] b) copolymerized units of one or more cure site comonomers selected from the group consisting of unsaturated carboxylic acids and anhydrides of unsaturated carboxylic acids.
[0059] The polyacrylate copolymer is preferably amorphous. The term "amorphous" as used herein to describe the polyacrylate copolymer refers to a copolymer that exhibits little crystalline structure at room temperature in an unstressed state. Alternatively, the amorphous material has a heat of fusion of less than 4 J / g, as determined according to ASTM D3418-08.
[0060] Preferred polyacrylate copolymers comprise copolymerized units of a) at least one alkyl or alkoxyalkyl acrylate and b) a cure site monomer. Examples of suitable alkyl and alkoxyalkyl acrylates include alkyl acrylates and alkoxyalkyl acrylates and acrylates in which acrylic acid is replaced by a C1-C 10 Alkyl substituted substances. Examples of such substances include alkyl methacrylates, alkyl ethylacrylates, alkyl propylacrylates, and alkyl hexylacrylates, alkoxyalkyl methacrylates, alkoxyalkyl ethylacrylates, alkoxyalkyl propylacrylates, and alkoxyalkyl hexylacrylates. Polyacrylate copolymers may also contain copolymerized units of more than one alkyl ester or alkoxyalkyl ester (e.g., two alkyl acrylates), or may contain α-olefins, such as propylene, 1-butene, 1-hexene, etc.
[0061] The alkyl and alkoxyalkyl esters of acrylic acid and substituted acrylic acid are preferably C1-C1 12 Alkyl esters, or C1-C 20 Alkoxyalkyl esters. Preferred examples of esters include methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, butyl acrylate, butyl methacrylate, 2-ethylhexyl acrylate, 2-methoxyethyl acrylate, 2-ethoxyethyl acrylate, 2-(n-propoxy)ethyl acrylate, 2-(n-butoxy)ethyl acrylate, 3-methoxypropyl acrylate, and 3-ethoxypropyl acrylate. More preferably, the ester group includes a branched or unbranched C1-C8 alkyl. Still more preferably, the ester group includes a unbranched C1-C4 alkyl. Still more preferred (meth)alkyl acrylates include methyl acrylate, methyl methacrylate, ethyl acrylate, and butyl acrylate.
[0062] The amount of acrylate comonomer in the polyacrylate copolymer is at least 45 wt % or at least 50 wt % based on the total weight of the polyacrylate copolymer. Preferably, the concentration will be at least 55 wt %, and more preferably at least 60 wt %. If the concentration of acrylate is less than 45 wt % or 50 wt %, there is a high probability that some crystallinity exists, such as in the polyethylene / acrylate rubber described below. Crystallinity in the polyacrylate copolymer or polyethylene / acrylate rubber can reduce the elastic properties of the reaction product of the polyacrylate copolymer or polyethylene / acrylate rubber with the aminosilane, or it can reduce the elastic properties of the polymer blend.
[0063] The polyacrylate copolymers useful in the practice of the present invention further comprise copolymerized cure site monomer units selected from the group consisting of unsaturated carboxylic acids, anhydrides of unsaturated carboxylic acids, unsaturated epoxides, and mixtures of two or more thereof. These cure site monomer units contain functional groups that can react with amines or other nitrogen-containing species such as carbamates.
[0064] Suitable unsaturated carboxylic acids include, but are not limited to, acrylic acid and methacrylic acid, 1,4-butenedioic acid, citraconic acid, and monoalkyl esters of 1,4-butenedioic acid. 1,4-Butenedioic acid may exist in the cis or trans form or in a mixture of both prior to polymerization, such as maleic acid or fumaric acid. Suitable cure site comonomers also include anhydrides of unsaturated carboxylic acids, such as maleic anhydride, citraconic anhydride, and itaconic anhydride. Preferred cure site monomers include maleic acid and any of its half acid esters (monoesters) or diesters, particularly methyl or ethyl half acid esters (e.g., monoethyl maleate); fumaric acid and any of its half acid esters or diesters, particularly methyl, ethyl, or butyl half acid esters; and monoalkyl esters and monoarylalkyl esters of itaconic acid. Preferred polyacrylate copolymers contain from 0.3 wt% or 0.5 wt% to 10 wt%, or from 1.0 wt% or 1.5 wt% to 8 wt%, or from 1.7 wt% or 2 wt% to 5 wt% copolymerized residues derived from one or more cure-site comonomers.
[0065] Preferred polyacrylate copolymers consist of or consist essentially of copolymerized units of one or more acrylates and one or more cure site comonomers.
[0066] Suitable acrylate copolymers are available under the trade name HyTemp TM Elastomers (manufactured by Zeon Chemicals LP, of Louisville, KY) are commercially available and are marketed as Noxtite TMACM acrylic rubber was obtained from Unimatec Chemicals America, Inc., of Novi, MI.
[0067] Polyethylene / acrylate rubbers are a class of preferred polyacrylate copolymers. In addition to comprising one or more acrylates and one or more cure site comonomers as described above and in the amounts described above, suitable polyethylene / acrylate rubbers further comprise 85 mol % or less, or 82 mol % or less, of copolymerized units derived from ethylene, based on the total moles of comonomer units in the polyethylene / acrylate rubber.
[0068] Preferred polyethylene / acrylate rubbers contain 45 wt% or more, or 50 wt% or more copolymerized residues derived from one or more alkyl acrylates, and at least 0.1 mol%, 0.3 mol% or 0.5 mol% copolymerized residues derived from one or more cure site comonomers, based on the total weight of the polyethylene / acrylate rubber. More preferably, the polyethylene / acrylate rubber contains 45 wt% to 80 wt%, or 50 wt% to 70 wt%, or 50 wt% to 65 wt% copolymerized residues derived from one or more alkyl acrylates. Preferred are branched or unbranched alkyl groups containing 1 to 6 carbon atoms, and more preferably are unbranched alkyl groups containing 1 to 4 carbon atoms. In addition, preferred polyethylene / acrylate rubbers contain 0.3 wt% or 0.5 wt% to 10 wt%, or 1.0 wt% or 1.5 wt% to 8 wt%, or 1.7 wt% or 2 wt% to 5 wt% copolymerized residues derived from one or more cure site comonomers. The balance of the polyethylene / acrylate rubber consists of or consists essentially of copolymerized units of ethylene.
[0069] Suitable polyethylene / acrylate rubbers are available from E.I. DuPont Specialty Products LLC, Wilmington, Delaware, as Trademark commercially available.
[0070] Suitable aminosilanes have at least one hydrolyzable group attached to the silicon atom, such as an alkoxy group, an acetoxy group or a halogen group, preferably an alkoxy group. Preferably, there are at least two such hydrolyzable groups capable of undergoing a crosslinking condensation reaction. The amine moiety must have a sufficient reaction rate with the cure site comonomer. Typically, tertiary amines react slowly with the preferred cure site comonomers and are therefore less favorable. A mixture of two or more different aminosilanes can be used.
[0071] Aminosilane can be represented by the formula YNHBSi(OR) a (X) 3-a, wherein a=1 to 3, preferably 2 or 3; Y is hydrogen, alkyl, alkenyl, hydroxyalkyl, alkaryl, alkylsilyl, alkylamine, C(=O)OR or C(=O)NR; R is acyl, alkyl, aryl or alkaryl; X may be R or a halogen atom; B is a divalent bridging group, which is preferably an alkylene group. Suitable alkylene groups for B are unbranched, branched (e.g., neohexylene), or cyclic (e.g., cyclohexylene). B may contain a heteroatom bridge, such as an ether bond. Preferably, B is a propylene moiety (-C3H6-). Preferably, R is a methyl or ethyl group. Preferably, Y is an aminoalkyl, hydrogen, or alkyl group. More preferably, Y is hydrogen or a primary aminoalkyl group (e.g., aminoethyl). Preferably, X is a chlorine atom or a methyl group, more preferably a methyl group.
[0072] Preferred aminosilanes for reacting with the polyacrylate copolymer include, but are not limited to, (3-aminopropyl)trimethoxysilane, (3-aminopropyl)triethoxysilane, N-β-(aminoethyl)-γ-aminopropyl-trimethoxysilane, N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane, vinylbenzylaminoethylamino-propyltrimethoxysilane, bis(trimethoxysilylpropyl)amine, and mixtures of two or more thereof. Suitable aminosilanes are available from Dow Chemical Company of Midland, MI; MilliporeSigma of St. Louis, MO; and under the trade name SILQUEST TM Commercially available from Momentive Performance Materials, Inc., of Waterford, NY.
[0073] Without wishing to be bound by theory, it is assumed that the amine group of aminosilane reacts with dicarboxylic acid groups or derivatives to form imide groups along the main chain of polyacrylate copolymer. The silane group of aminosilane is suspended from the nitrogen of imide, and the imide is also derived from aminosilane reagent. It is further assumed that two or more silane side groups can react to form covalent silane-oxygen-silane bonds, wherein one or more XH or RH molecules such as alkanol, aryl alkanol, carboxylic acid or halogenated acid molecules are eliminated, thereby making polyacrylate copolymer crosslinked. Crosslinking can be formed by single-[-Si-O-Si-]-partially, or it can be formed by many alkoxysilane groups reacting to form a siloxane network comprising three or more silicon atoms. Such reactions are for example described by Xiangke Shi et al. in Silicon [Silicon] (2012) 4:109-119.
[0074] The molar ratio of aminosilane to dicarboxylic acid cure sites of the polyacrylate copolymer in the reaction mixture is preferably in the range of 0.2 to 1.5, more preferably in the range of 0.2 to 1.0, and even more preferably in the range of 0.25 to 0.8. Significantly, the addition of excessive amounts of aminosilane to the reaction mixture may result in poor surface appearance of the molded or extruded article due to premature crosslinking and insufficient dispersion of the polyacrylate copolymer in the polymer blend. Also significantly, the addition of insufficient amounts of aminosilane to the reaction mixture may result in the production of a viscous polymer blend that will be difficult to process if any.
[0075] The copolyether-ester polymer and the reaction product of the polyacrylate copolymer and the aminosilane may be combined in any relative amounts, depending on the desired properties of the polymer blend. Preferably, the ratio of the weight of the copolyether-ester polymer to the weight of the reaction product of the polyacrylate copolymer and the aminosilane will be between 0.5:1 and 19:1, or more preferably between 0.66:1 and 19:1, most preferably between 1:1 and 4:1, or between 1.5:1 and 4:1. Alternatively, the copolyester-ether is preferably present in the polymer blend at from about 30 wt% to 95 wt%, more preferably from 40 wt% to 95 wt%, and still more preferably from 50 wt% to 80 wt%, based on the sum of the weights of the copolyether-ester, polyacrylate copolymer, and aminosilane.
[0076] For the purpose of calculating the weight percent of the reaction product of the polyacrylate copolymer and the aminosilane, the weight of the reaction product is the same as the weight of the starting materials (i.e., the one or more polymers and the one or more aminosilanes added during the production of the polymer blend), ignoring the fate of a small amount of released molecules, which are typically alcohols and water produced by the condensation of silane groups and the reaction of amines with the carboxylic acid cure sites of the polyacrylate copolymer. Depending on the degree of devolatilization during the production of the polymer blend, these molecules may be removed or become part of the blend via transesterification.
[0077] The blend of the reaction product of the copolyether-ester polymer and the polyacrylate copolymer and the aminosilane may further comprise one or more other components of any type or content required to meet the technical requirements, such as additives, fillers, processing aids, plasticizers, stabilizers, viscosity modifiers, colorants, pigments. Particularly useful in durable applications are antioxidants, especially phenolic antioxidants, phosphite antioxidants, and amine-containing antioxidants. These one or more other components can be added at any stage during the production of the blend or in subsequent processing steps in an amount conventional in the art. The reaction between the aminosilane and the polyacrylate copolymer can be carried out during the blending process, for example in a double-roll rubber mill or by using an internal mixer suitable for compounding rubber compositions, including Banbury TM Internal mixer, Haake Rheocord TM Mixer, Brabender Plastograph TM Mixer, Farrell Continuous Mixer, Buss TM The extrusion is preferably carried out in a kneader, or in a single screw or twin screw extruder. A twin screw extruder is preferred. Preferably, one or more polyacrylate copolymers are fed to the extruder and subsequently one or more aminosilanes are injected into the polymer.
[0078] The extruder barrel temperature prior to aminosilane injection is preferably 150°C or less, while the barrel temperature downstream of the injection point is preferably 150°C or greater. Injecting the aminosilane with an extruder temperature set point of 150°C or less ensures that the aminosilane can mix with the polyacrylate copolymer before silane condensation occurs, which in turn improves the efficiency of aminosilane crosslinking so that less aminosilane is required to achieve a given cure state. At temperatures of 150°C or greater, the aminosilane is grafted onto the polyacrylate copolymer via reaction with the amines at the cure site, and the silane rapidly condenses to form crosslinks. The copolyester-ether polymer can be added at any point prior to extruder discharge. Preferably, the copolyester-ether polymer is added at a barrel temperature of 150°C or less so that silane condensation occurs substantially simultaneously with melting and mixing of the copolyester-ether polymer.
[0079] The one or more aminosilanes may be optionally diluted with one or more non-reactive solvents or carriers as desired. Suitable solvents and carriers include, but are not limited to, anhydrous toluene, anhydrous ethanol, and acetone. The concentration of the one or more aminosilanes in the one or more solvents or one or more carriers may range from about 10 wt % to about 95 wt % based on the total weight of the one or more aminosilanes and the one or more solvents or one or more carriers.
[0080] The extruder screw design should be sufficient to uniformly mix the liquid aminosilane with the polymer at the injection point and downstream. In the extruder screw section where the polyacrylate is crosslinked, a high work element such as a kneading block is preferably used to ensure that the crosslinked elastomer is dispersed in the copolyether-ester polymer. Other screw elements such as reverse elements, gear mixers, propulsion elements and bubble rings are well known to those skilled in the art of reactive extrusion and are used to control the degree of mixing, temperature and residence time of the polymerized reaction mixture, reaction product or blend in the extruder. Preferably, the extruder has at least one vacuum exhaust port to extract volatiles generated by the curing reaction. The extruder screw speed can vary over a wide range, typically from 200RPM to 600RPM, more preferably from 250RPM to 400RPM. Preferably, the barrel temperature is set between 100°C and 240°C.
[0081] Catalysts for accelerating the reaction occurring during the production of the polymer blend can also be added at any point in the method. For example, a catalyst suitable for accelerating the reaction of the curing site of the amine and the polyacrylate copolymer is preferably added before, simultaneously or substantially simultaneously with the addition of the aminosilane, so that the curing site of the aminosilane and the polyacrylate copolymer reacts before the condensation of the silane forms a siloxane bond. Suitable catalysts are well known in the art as accelerators for polyamine curing of polyacrylate copolymers. For example, some suitable catalysts are described in U.S. Patent No. 3,883,472. Tertiary amines constitute a class of catalysts preferably used to accelerate the grafting of aminosilanes to polyacrylate copolymers. A particularly preferred catalyst is 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU). Preferably, the polymer blend contains at least an effective amount of a catalyst to accelerate the reaction of the curing site of the amine and the polyacrylate copolymer. The catalyst may be present in an amount of 1 part by weight (pbw) to 50pbw based on the weight of the aminosilane. More preferably, the catalyst is present in an amount of 1pbw per 5pbw of aminosilane.
[0082] Catalysts for accelerating the formation of siloxane bonds may also be added at any point during the production of the polymer blend. Suitable catalysts are well known in the art, such as S. Levigoureux, P. Garcia, M. Ficquenet, and I. Denizet, "Catalyst alternatives to replace DBTDL and crosslink speed improvement of a low voltage cable insulation", 9th International Conference on Insulated Power Cables, Versailles, France, June 2015. Such catalysts include sulfonic and carboxylic acids, metal hydroxides, and organotin compounds. However, catalysts for siloxane formation are preferably absent from the polymer blend, at least in part because these catalysts may catalyze undesirable hydrolysis or alcoholysis of the copolyester-ether polymer as water and alcohol are released from the silane condensation and reaction of the amine with the elastomer cure site.
[0083] The process conditions and aminosilane levels for preparing the polymer blends described herein can be changed to achieve a wide range of technical goals. Insufficient crosslinking of polyacrylate copolymers can produce blends that are too sticky to granulate, or if granulated, the blend may experience aggregation or agglomeration of pellets. These problems can be solved by increasing the aminosilane content, by including a catalyst to increase the reaction rate of the amine and elastomer cure site, or by changing the addition conditions of the aminosilane to ensure that the aminosilane becomes fully mixed with the polyacrylate copolymer before initiating silane condensation. As a general rule, the tensile strength and ductility of the blend are optimal when the aminosilane content is slightly greater than the minimum amount required for producing non-aggregated pellets. Higher aminosilane content tends to increase the modulus of the blend while reducing ductility.
[0084] Scientists and engineers in the field of reactive extrusion can apply the conventional principles of extruder operation, screw design and methods for feeding raw materials to the extruder to obtain acceptable operating parameters, thereby meeting the technical requirements for producing the polymer blends described herein. For example, the design of the aminosilane injection system is preferably anti-blocking and provides a continuous and stable flow. The extruder screw is preferably combined with an element such as a kneading block to quickly and evenly mix the aminosilane into one or more polymers. Reverse elements and gear mixers can be used to increase the residence time in this section to ensure the grafting of aminosilane and elastomer. The screw sections involved in the melting and mixing of copolyether-ester copolymers with polyacrylate copolymers and aminosilanes should be combined with kneading blocks, reverse elements or other high-power elements to ensure the good dispersion of elastomers in copolyether-ester copolymers. As well known to those skilled in the art, extruder feed rate, output, screw RPM and melt temperature also affect residence time and mixing. Typical extruder screw speeds can be in the range of 100RPM to 500RPM, more typically in the range of 200RPM to 400RPM. The polymer temperature at the extruder outlet is typically in the range of 240 to 315°C, 240 to 300°C, preferably 250 to 290°C.
[0085] In addition, the polymer blend thus obtained can be post-processed by solid state polymerization to increase viscosity. In this technique, the polymer blend is exposed to a temperature of about 10°C to 40°C below the melting peak temperature of the copolyether-ester polymer for a sufficient time to promote esterification of residual hydroxyl and carboxylic acid residues, thereby increasing the viscosity of the polymer blend.
[0086] The polymer blends may be characterized by a variety of morphologies ranging from discrete crosslinked elastomer particles dispersed within the copolyester-ether polymer matrix to a cocontinuous phase comprising a lightly crosslinked elastomer and copolyester-ether, to mixtures of these morphologies. Some of these morphologies may not be suitable for use in the articles described herein because they may render the material difficult to further compound, or because they may exhibit poor elastic properties, such as a tensile elongation at break of less than 100%, or because they may exhibit poor aging behavior, or because the morphology is unstable, for example, it may become coarse when the polymer blend is held stationary above the melting peak temperature of the copolyester-ether copolymer. Most preferably, the reaction product of the aminosilane and the polyacrylate copolymer is present in the polyester-ether block copolymer as discrete particles. In this morphology, the polymer blend is a thermoplastic vulcanizate or TPV.
[0087] Typically, the distribution and dispersion of the reaction product in the copolyether-polyester block copolymer can be evaluated by molding a test tensile specimen and measuring the tensile strength of the polymer blend. The mechanical properties of the polymer blend can be evaluated using a load frame such as an Instron tensile tester according to ISO-527-1 (2019) using an injection molded 5A sample and a traction speed of 20 mm / min. The poor dispersion of the reaction product of aminosilane and polyacrylate copolymer reduces the tensile strength of the blend. Although the tensile strength also varies with the type and content of the copolyester-ether polymer in the blend, those of ordinary skill in the art can apply these principles and techniques to optimize the blend properties.
[0088] Preferred polymer blends exhibit stable morphology when kept stationary at a temperature higher than the melting peak temperature of the copolyester-ether copolymer. Blends with unstable morphology show significant roughening, lump formation or other deformation of the extrudate under these conditions. The stability of the blend morphology can be evaluated using a single screw extruder equipped with a strip die. The tested blend composition is extruded at a consistent rate, and a sheet or strip sample is collected. Then, one or more extruder screws are stopped for a period of time, while the blend is kept at a certain temperature, and a second sample is collected immediately when the extruder is restarted. Most preferably, the two extrudates have a visually smooth appearance, and the static dwell period does not change. Less preferably, the initial sample is smooth, while the second sample is rough, blocky or deformed. Least preferably, both samples show rough, blocky or deformed extrudates.
[0089] By varying the type and weight ratio of the copolyether-ester copolymer and the polyacrylate copolymer, the polymer blends described herein can range from soft (about 60 Shore A) highly elastic thermoplastic elastomers to harder (about 70 Shore D) flexible plastics. In general, the strength and stiffness of the polymer blends decrease with increasing content of the elastomer reaction product polyacrylate copolymer and aminosilane, while resistance to hot air and hot water aging improves. The polymer blends of the invention described herein show excellent resistance to hot air and hot water aging compared to pure copolyester-ether polymers of the same hardness.
[0090] The polymer blends described herein can be used in a variety of industrial applications, for example, for the production of articles including: wire and cable jacketing; consumer electronics; consumer products such as footwear; oil and gas flat packs; air ducts and shields for transportation vehicles such as automobiles, including inboard and outboard CVJ (continuous velocity joint) shields, diaphragm shields, and drive shaft shields; soft touch, wear resistance and sealing applications; fluid and air ducts for transportation vehicles such as automobiles; and other articles in the fields of automotive, fluid power (such as fluid power transmission lines), electrical / electronics, hoses and pipes, and appliances.
[0091] These articles can be produced using conventional methods for making articles from thermoplastic polymer materials, such as, for example, injection molding, blow molding, extrusion, compression molding, compression blow molding (Ossberger molding), accumulator blow molding, extrusion blow molding, or injection-blow molding.
[0092] The following examples are provided to further describe the present invention in detail. These examples, which set forth preferred modes presently considered for carrying out the invention, are intended to illustrate but not to limit the invention.
[0093] Examples
[0094] Material
[0095] Copolyester-ether A comprises copolymerized residues of 2000 g / mol PTMEG (72.5 wt%), terephthalic acid (18.4 wt%) and 1,4-butanediol (9.1 wt%). The polymer comprises about 22.6 wt% short chain ester units (hard segments) and 77.4 wt% long chain ester units (soft segments) and has a melting peak temperature of 177°C.
[0096] Copolyester-ether B comprises copolymerized residues of 1000 g / mol PTMEG (7.8 wt%), terephthalic acid (55.8 wt%) and 1,4-butanediol (36.4 wt%). The polymer comprises about 91 wt% short chain ester units and 9 wt% long chain ester units and has a melting peak temperature of 221°C.
[0097] Copolyester-ether C comprises copolymerized residues of 2000 g / mol PTMEG (50.6 wt%), terephthalic acid (31 wt%) and 1,4-butanediol (18.4 wt%). The polymer comprises about 46 wt% short chain ester units and 54 wt% long chain ester units, and is subjected to a solid state polymerization process to increase the molecular weight. The polymer has a melting peak temperature of 198°C.
[0098] Polyethylene / acrylate rubber A contains 55 wt% copolymerized units of methyl acrylate, 3.1 wt% copolymerized units of a cure site monomer having carboxylic acid functionality, and the balance copolymerized units of ethylene. The polymer is amorphous and does not exhibit a melting peak temperature.
[0099] Polyethylene / acrylate rubber B comprises 23 wt% copolymerized units derived from methyl acrylate, 41 wt% copolymerized units derived from butyl acrylate, 3.2 wt% copolymerized units of a cure site comonomer having carboxylic acid functionality, and the balance copolymerized units of ethylene. The polymer is amorphous and does not exhibit a melting peak temperature.
[0100] Polyacrylate Copolymer A comprises 54 wt% ethyl acrylate, 44 wt% butyl acrylate and 2 wt% cure site monomer having carboxylic acid functionality. The polymer is amorphous and does not exhibit a melting peak temperature.
[0101] PBT is polybutylene terephthalate, available from DuPont deNemours, Inc., of Wilmington, Delaware as 6129 obtained.
[0102] Aminosilane A is 3-aminopropyltriethoxysilane, available from Sigma-Aldrich Corporation
[0103] Aminosilane B is 3-aminopropyltrimethoxysilane, available from Sigma-Aldrich
[0104] The diamine was 2,2,4(2,4,4)-trimethyl-1,6-hexanediamine, available from Sigma-Aldrich
[0105] DBU is a tertiary amine catalyst 1,8-diazabicyclo[5.4.0]undec-7-ene, available from Sigma-Aldrich
[0106] Test Method
[0107] Prior to injection molding, the pellets were dried in a vacuum oven at 80°C to 90°C overnight or for at least 4 hours or 6 hours. The materials were injection molded on an Arburg 1.5 oz machine. The barrel temperature was set above the melting peak temperature of the copolyether-ester polymer as determined by the method of ASTM D3418-15.
[0108] The tensile properties (tensile strength, elongation at break) of the polymer blends were measured by Instron TM The tensile tester was evaluated according to ISO-527-1 (2019) using an injection molded 5A bar and a pulling speed of 20 mm / min. The flexibility of the polymer blends was evaluated by Instron TM The flexural modulus tester was evaluated according to ISO-178 (2019) using an injection molded 4 mm multi-purpose rod and a test speed of 1.270 mm / min. The hardness (Shore A and Shore D) of the polymer blends was evaluated using the standard conditions described in ISO-868 (2003) with certain modifications, where an injection molded 4 mm multi-purpose rod or 5A rod was used to report the peak (initial) hardness after 15 seconds instead of the hardness. All samples were adjusted according to their ISO standards.
[0109] The extrusion quality and stability of the polymer blends were evaluated using a 19.1 mm diameter single screw extruder equipped with a 25.4 mm x 0.8 mm strip die. The extruder barrel had three heating zones and the die had a single heating zone. The temperature was set as described in the examples, typically increasing from the feed zone to the die, with the final extruder and die temperatures set to about 20°C higher than the melting peak temperature of the copolyether-ester copolymer in the tested blend. Extrusion quality was evaluated by collecting two types of air-cooled extruded strips:
[0110] Strip 1 - collected with the extruder running at 25 rpm steady state.
[0111] Strip 2 - After collecting Strip 1, the screw was stopped for 5 minutes and then restarted at 25 rpm. Strip 2 is the extrudate collected immediately upon start-up.
[0112] The appearance of the strips was visually assessed according to the following description:
[0113] Smooth surface with a shiny appearance without bumps, lumps, ripples or other defects
[0114] Matte finish has a dull appearance but is otherwise free of defects
[0115] Rough surface has ridges, ripples, masses or other defects that may be continuous or intermittent.
[0116] Examples E1, E2 and E3 in Table I demonstrate the use of copolyester-ether copolymers with high soft segment content to produce low hardness thermoplastic elastomers with good physical properties and extrusion quality. These examples further demonstrate the advantages of using a catalyst in combination with an aminosilane. The polymer blends in Table I were produced using a 30 mm co-rotating twin screw extruder with 12 barrel zones operating at 300 rpm and 10.9 kg / hr output rate. The copolyester-ether copolymer was fed to barrel zone 1, the polyethylene / acrylate rubber was fed to barrel zone 4, and the aminosilane or diamine crosslinker was fed to barrel zone 5. The temperature setting point for barrel zones 1 to 7 was 100°C, while barrel zones 8 to 12 were set to 220°C. The polymer blends were extruded through a strand die set at 220°C, and the resulting strands were cooled in a water bath and pelletized. Where a catalyst was used, it was premixed with the aminosilane or diamine.
[0117] The extrusion quality of the polymer blends in Table I was evaluated using a single screw extruder with a temperature profile at temperature settings of 170° C., 180° C., and 190° C. (feed zone to discharge) and a strip die with a temperature setting of 190° C. The polymer blends of Examples E1, E2, and E3 extruded smoothly (Strip 1 and Strip 2) both before and after the 5 minute extruder pause, while Strip 2 of Comparative Example CE1 was rough and of poor quality.
[0118] The combination of DBU catalyst and aminosilane in Examples E1 and E3 produces polymer blends with better tensile strength than blends containing only aminosilane (E2) or blends containing a combination of DBU catalyst and diamine (CE1). The use of DBU catalyst also reduces the aminosilane content required to produce non-sticky free-flowing pellets. Examples E1, E2, and E3 use the minimum aminosilane content required to produce free-flowing pellets. In the absence of catalyst, E2 requires more than 20% more primary amine equivalents from aminosilane than E1 or E3.
[0119] Table I
[0120]
[0121]
[0122] mol amine / Kg elastomer 0.095 0.122 0.103 0.082
[0123] Shore A Hardness (Peak) 71 68 71 69 Tensile strength at break (MPa) 13.6 12.3 15.1 12.8 Elongation at break (%) 320 395 390 365
[0124] Extruded strip 1 smooth smooth smooth smooth Extruded strip 2 smooth smooth smooth Rough
[0125] Example 2
[0126] The polymer blends in Table II were produced according to the process conditions described in Example 1 with one exception: the temperature of the twin screw extruder barrel zones 8 to 12 was increased from 220° C. to 240° C. The tape extrusion used a temperature profile of 220° C., 230° C. and 240° C. (feed zone to discharge) and a tape die set at 240° C. to accommodate the higher melt peak temperature of copolyester-ether B.
[0127] Examples E4 and E5 in Table II demonstrate the use of copolyester-ether copolymers with low soft segment content with or without DBU catalyst. Consistent with the results in Example 1, the combination of DBU catalyst and aminosilane allows the use of lower aminosilane levels while increasing the tensile strength and elongation at break of the polymer blends. Both E4 and E5 exhibit excellent tape extrusion quality with no roughening after a five minute dwell (Extruded Tape 2).
[0128] Comparative Example CE2 uses a conventional diamine curing agent and exhibits poor extrusion quality in Extruded Strip 2. Comparative Example CE3 replaces the copolyester-ether copolymer of E4 with a polybutylene terephthalate homopolymer (PBT). Surprisingly, even though the copolyester-ether B differs from PBT in composition by the presence of only 7.8 wt% PTMEG, CE3 exhibits much poorer flexibility and ductility than E4. Because the present invention aims to provide solutions for polymer blends tailored for demanding solutions, the use of copolyester-ether copolymers provides much greater formulation flexibility than homopolymer polyesters.
[0129] Table II
[0130] E4 E5 CE2 CE3 wt% wt% wt% wt% Copolyester-ether B 49.53 49.5 49.8 PBT 49.53 Polyethylene / Acrylic Rubber A 49.53 49.5 49.8 49.53 Diamine 0.4 Aminosilane A 0.82 1 0.82 DBU Catalyst 0.12 0.12
[0131] mol amine / Kg elastomer 0.075 0.091 0.101 0.075
[0132] Tensile strength at break (MPa) 19.7 16.9 16.9 19.8 Elongation at break (%) 210 185 160 145 Flexural modulus (MPa) 360 305 260 585
[0133] Extruded strip 1 smooth smooth smooth smooth Extruded strip 2 smooth smooth Rough smooth
[0134] Example 3
[0135] The polymer blends in Table III demonstrate the use of copolyester-ether copolymers blended with polyacrylate copolymers that have been solid state polymerized to increase molecular weight. Examples E6 and E7 were prepared according to the process in Example 1. The tape extrusion used a temperature profile of 200°C, 210°C, and 220°C (feed zone to discharge) and a tape die set at 220°C.
[0136] The results in Table III show that E6, which uses polyethylene / acrylate rubber, has higher strength and ductility than E7, which is based on a polyacrylate copolymer. Both E6 and E7 exhibit good tape extrusion characteristics, with no degradation in surface finish between tape 1 and tape 2, though E6 exhibits a smooth finish and E7 has a matte finish. Both are acceptable, although one or the other may be preferred in certain applications.
[0137] Table III
[0138] E6 E7 wt% wt% Copolyester-ether C 69.63 69.63 Polyethylene / Acrylic Rubber B 29.83 Polyacrylate copolymer A 29.83 Aminosilane A 0.47 0.47 DBU Catalyst 0.07 0.07
[0139] mol amine / Kg elastomer 0.071 0.071
[0140] Shore D hardness (peak) 37 37 Tensile strength at break (MPa) 16.6 13 Elongation at break (%) 275 210
[0141] Extruded strip 1 smooth Matte Extruded strip 2 smooth Matte
[0142] Although certain preferred embodiments of the present invention have been described and specifically illustrated above, it is not intended to limit the present invention to such embodiments. Various modifications may be made without departing from the scope and spirit of the present invention, as set forth in the following claims.
Claims
1. A polymer blend comprising: (a) a copolyether-ester copolymer comprising copolymerized residues of a polyalkylene terephthalate and copolymerized residues of a polyether glycol; and (b) a reaction product of a polyacrylate copolymer and an aminosilane; wherein i) the polyacrylate copolymer comprises at least 0.3 wt% of copolymerized residues of a cure site comonomer, wherein the sum of the weight percentages of the copolymerized residues in the polyacrylate copolymer is 100 wt%; and wherein, ii) the polymer blend comprises from 5 wt% to 70 wt% of the reaction product of the polyacrylate copolymer and the aminosilane, based on the total weight of the polymer blend.
2. The polymer blend according to claim 1, wherein The copolyether-ester copolymer comprises copolymerized units of polybutylene phthalate.
3. The polymer blend according to claim 1, wherein The copolyether-ester copolymer comprises from 5 wt % to 80 wt % of copolymerized residues of one or more polyether diols, based on the total weight of the copolyether-ester copolymer.
4. The polymer blend according to claim 1, wherein The copolyether-ester copolymer further comprises copolymerized residues of polyalkylene isophthalate.
5. The polymer blend according to claim 1, wherein The copolyether-ester copolymer comprises copolymerized units of polybutylene isophthalate.
6. The polymer blend according to claim 1, wherein The polyacrylate copolymer further comprises copolymerized residues of ethylene.
7. The polymer blend according to claim 1, wherein The polyacrylate copolymer comprises, based on the total weight of the polyacrylate copolymer, 0.3 wt% to 10 wt% of copolymerized residues derived from one or more cure-site comonomers; 45 wt% to 80 wt% of copolymerized residues derived from one or more alkyl acrylates; and 10 wt% to 55 wt% of copolymerized residues derived from ethylene, wherein the sum of the weight percentages of all copolymerized residues in the polyacrylate copolymer is 100 wt%.
8. The polymer blend of claim 1, wherein The aminosilane is represented by the formula YNHBSi(OR) a (X) 3-a , wherein a is an integer equal to 1, 2 or 3; Y is a hydrogen atom or an alkyl, alkenyl, hydroxyalkyl, alkaryl, alkylsilyl, alkylamine, C(=O)OR or C(=O)NR group; R is an acyl, alkyl, aryl or alkaryl group; X is R or a halogen atom; and B is a divalent bridging group.
9. The polymer blend of claim 1, wherein: The aminosilane includes one or more compounds selected from the group consisting of: (3-aminopropyl)trimethoxysilane, (3-aminopropyl)triethoxysilane, N-β-(aminoethyl)-γ-aminopropyl-trimethoxysilane, N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane, vinylbenzylaminoethylamino-propyltrimethoxysilane, and bis(trimethoxysilylpropyl)amine.
10. The polymer blend according to claim 1, wherein The aminosilane is 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, or a combination of 3-aminopropyltriethoxysilane and 3-aminopropyltrimethoxysilane.
11. The polymer blend of any one of claims 1 to 10, further comprising: one or more other components selected from the group consisting of additives, fillers, processing aids, plasticizers, stabilizers, viscosity modifiers, colorants, pigments, and antioxidants.
12. The polymer blend of claim 11, wherein The antioxidant is selected from the group consisting of phenolic antioxidants, phosphite antioxidants, and amine-containing antioxidants.
13. The polymer blend of any one of claims 1 to 10 comprising a thermoplastic vulcanizate.
14. The polymer blend of any one of claims 1 to 10 comprising at least an effective amount of a catalyst to accelerate the reaction of an amine with the cure sites of the polyacrylate copolymer.
15. The polymer blend of claim 14, wherein The catalyst is a tertiary amine.
16. The polymer blend of claim 14, wherein The catalyst is 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU).
17. A method for preparing a polymer blend as claimed in any one of claims 1 to 16, comprising the following steps: a) mixing one or more polyacrylate copolymers with an aminosilane to form a composition; as well as b) melt mixing one or more copolyether-ester copolymers with the composition.
18. The method of claim 17, wherein: Step (a) is carried out at a temperature of less than 150°C.
19. The method of claim 17, wherein: Step (b) is carried out at a temperature of 150°C or higher.
20. The method of claim 17, wherein: Steps (a) and (b) are carried out sequentially in a twin-screw extruder.
21. A method for preparing a polymer blend as claimed in any one of claims 1 to 16, comprising the steps of: a) melt mixing one or more polyacrylate copolymers with one or more copolyether-ester copolymers to form a composition; and b) melt mixing the composition of step (a) with an aminosilane.
22. A method for preparing a polymer blend as claimed in any one of claims 1 to 16, wherein: The polyacrylate copolymer is combined with the aminosilane and the copolyether-ester copolymer in a melt to form a melt comprising the copolyether-ester copolymer and a reaction product of the polyacrylate copolymer and the aminosilane, and wherein the melt is cooled to form the polymer blend.
23. An article comprising the polymer blend of any one of claims 1 to 16, the article being selected from the group consisting of: a consumer electronic product comprising: Power cord jacketing and strain relief; consumer products, including footwear outsoles and midsoles; soft-touch overmolding for power tools and other handheld devices; Wearable applications, including belts or strips; sealing applications, including automotive intake manifold gaskets; wire and cable applications, including boots; oil and gas flat packs; shields for transportation vehicles, including inboard and outboard CVJ shields, driveshaft shields, and diaphragm shields; fluid ducts and air ducts for transportation vehicles; and other articles used in the fields of transportation, automotive, fluid power, electrical, electronic, hose and pipe, and appliances.
24. The article of claim 23 produced by a process selected from the group consisting of injection molding, blow molding, extrusion, compression molding, and additive manufacturing.
25. The article of claim 23, produced by a process selected from the group consisting of compression-blow molding, accumulator blow molding, extrusion blow molding, and injection-blow molding.
Citation Information
Patent Citations
Fast curing heat stable elastomeric compositions
US3883472A
Silane vulcanized thermoplastic elastomers
US6448343B1
Curable thermoplastic elastomeric blend, method of manufacture, and use thereof
US7074857B2
Heat-stabilized acrylate elastomer composition and process for its production
US8779044B2
Curable thermoplastic elastomeric blend, method of manufacture, and use thereof
WO2004029155A2